A Highly Active and Support‐Free Oxygen Reduction Catalyst Prepared from Ultrahigh‐Surface‐Area Porous Polyporphyrin1. Issue 32 (26th June 2013) - Yuan, Shengwen; Shui, Jiang‐Lan; Grabstanowicz, Lauren; Chen, Chen; Commet, Sean; Reprogle, Briana; Xu, Tao; Yu, Luping; Liu, Di‐Jia
<x xml:space="preserve">Abstract</x> An electrocatalyst for the oxygen reduction reaction that is free of precious metals was prepared by thermal activation of an ultrahigh‐surface‐area porous polyporphyrin. The PEM fuel cells made with such catalyst demonstrated excellent current and power densities.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>